The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5194/hess-21-3377-2017
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: An experimental set-up to measure latent and sensible heat fluxes from (artificial) plant leaves

Abstract: Abstract. Leaf transpiration and energy exchange are coupled processes that operate at small scales yet exert a significant influence on the terrestrial hydrological cycle and climate. Surprisingly, experimental capabilities required to quantify the energy-transpiration coupling at the leaf scale are lacking, challenging our ability to test basic questions of importance for resolving large-scale processes. The present study describes an experimental set-up for the simultaneous observation of transpiration rate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…Model outputs were validated using a leaf replica with a known conductance to water vapor subjected to the same fluctuating conditions. Although leaf replicas have been used in the past to study the importance of mass transfer in leaf energy balance (Zwieniecki et al , 2016; Schymanski and Or, 2017; Schymanski et al , 2017), our results highlight the potential of the low-cost leaf replica and references to validate leaf temperature predictions obtained using energy balance equations. The ability to derive g sw from thermography under a fluctuating environment using a relatively simple set-up opens the way to field measurements in the future, but will require further improvements to take into consideration parameters such as leaf orientations and local variations in L d .…”
Section: Discussionmentioning
confidence: 75%
“…Model outputs were validated using a leaf replica with a known conductance to water vapor subjected to the same fluctuating conditions. Although leaf replicas have been used in the past to study the importance of mass transfer in leaf energy balance (Zwieniecki et al , 2016; Schymanski and Or, 2017; Schymanski et al , 2017), our results highlight the potential of the low-cost leaf replica and references to validate leaf temperature predictions obtained using energy balance equations. The ability to derive g sw from thermography under a fluctuating environment using a relatively simple set-up opens the way to field measurements in the future, but will require further improvements to take into consideration parameters such as leaf orientations and local variations in L d .…”
Section: Discussionmentioning
confidence: 75%
“…Such independent control may help to prevent excess water loss from the mesophyll positioned in close proximity of open stomata on the sunlit leaf side. Substantial differences in surface temperatures between sunlit (nontranspiring) and shaded transpiring sides of leaves have been found through detailed modelling of the leaf energy balance (0.2–0.3°C; Buckley et al ., ) and through experiments with leaf replicas (Schymanski et al ., ). The wider occurrence of independent control on adaxial vs abaxial stomatal conductance, as well as the potential benefit in terms of water‐use efficiency, remain to be determined.…”
Section: Prospective Future Researchmentioning
confidence: 97%
“…The interaction between stomatal distribution and leaf temperature also has the potential to influence photosynthetic efficiency under specific conditions. By spatially separating evaporative cooling from light absorption and photosynthesis, hypostomatous leaves could reduce transpiration, thereby increasing longwave and sensible heat emissions (Schymanski et al ., ) and, when leaf temperature is below optimal, slightly increase photosynthetic efficiency on the slightly warmer sun‐exposed leaf side. By contrast, the amphistomatous leaf morphology may achieve slight increases in photosynthetic efficiency when leaf temperature is above optimal (as is more likely in arid environments) by spatially coupling evaporative cooling to the photosynthetically active tissue.…”
Section: Prospective Future Researchmentioning
confidence: 99%
“…The standard deviations of the MODIS Aqua day-night overpass time over the study sites were found to be within 30-45 min (Sharifnezhadazizi et al, 2019), and the expected deviation in LST from the mean local time would be around ±0. 75 K (Sharifnezhadazizi et al, 2019).…”
Section: Possible Sources Of Errors In Seb Flux Evaluationmentioning
confidence: 85%